Answer:
Explanation:
AB:
d = sqrt ( (−5−2)^2 + (−2−(−8))^2)
d = sqrt( (−7)^2 + (6)^2 )
d = sqrt(49+36)
d = sqrt(85)
d = 9.219544
BC:
d = sqrt ( (−7−(-5))^2+(3−(−2))^2 )
d = sqrt( (−2)^2 + (5)^2 )
d = sqrt(4+25)
d = sqrt(29)
d = 5.385165
AC:
d = sqrt ( (−7−(2))^2+(3−(−8))^2 )
d = sqrt( (−9)^2 + (11)^2 )
d = sqrt(81+121)
d = sqrt(202)
d = 14.21267
DE:
d = sqrt ( (−11−(-9))^2+(12−7)^2 )
d = sqrt( (−2)^2 + (5)^2 )
d = sqrt(4+25)
d = sqrt(29)
d = 5.385165
EF:
d = sqrt ( (−2−(-11))^2+(1−12)^2 )
d = sqrt( (9)^2 + (-11)^2 )
d = sqrt(81+121)
d = sqrt(202)
d =14.21267
DF:
d = sqrt ( (−2−(-9))^2+(1−7)^2 )
d = sqrt( (7)^2 + (-6)^2 )
d = sqrt(49+36)
d = sqrt(85)
d = 9.219544
Yes, the triangles are congruent because the lengths are the same.